2018
DOI: 10.1039/c8nr00455b
|View full text |Cite
|
Sign up to set email alerts
|

Light trapping in thin film silicon solar cells via phase separated disordered nanopillars

Abstract: In this work, we have improved the absorption properties of thin film solar cells by introducing light trapping reflectors deposited onto self-assembled nanostructures. The latter consist of a disordered array of nanopillars and are fabricated by polymer blend lithography. Their broadband light scattering properties are exploited to enhance the photocurrent density of thin film devices, here based on hydrogenated amorphous silicon active layers. We demonstrate that these light scattering nanopillars yield a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…While various aspects of diffractive behaviour of ED and MD resonances in arrays of NPs have been heavily studied in the recent decade [57][58][59][60], just a few works have addressed the effects of positional and size disorders [61][62][63], and only for arrays with purely ED coupling. Quite interesting results have also been reported for lasing [64,65] and solar energy harvesting [62,[66][67][68] in various types of quasi-periodic and aperiodic structures. However, it is a well known fact that the presence of imperfections in 1D chains of NPs [69,70], 2D structures [71][72][73][74][75][76], 3D metamaterials [77], and fractal aggregates [78] may lead to various intriguing effects.…”
Section: Introductionmentioning
confidence: 89%
“…While various aspects of diffractive behaviour of ED and MD resonances in arrays of NPs have been heavily studied in the recent decade [57][58][59][60], just a few works have addressed the effects of positional and size disorders [61][62][63], and only for arrays with purely ED coupling. Quite interesting results have also been reported for lasing [64,65] and solar energy harvesting [62,[66][67][68] in various types of quasi-periodic and aperiodic structures. However, it is a well known fact that the presence of imperfections in 1D chains of NPs [69,70], 2D structures [71][72][73][74][75][76], 3D metamaterials [77], and fractal aggregates [78] may lead to various intriguing effects.…”
Section: Introductionmentioning
confidence: 89%
“…For instance, it has been shown that the structure factor of dispersed colloidal particle (e.g. beads) patterns can be tuned by the ionic strength of the particular solvent 65,66 and that the dewetting of semiconductor layers leads to HUD patterns. 67 Also, soft-imprint conformal lithography has proven an excellent low-cost alternative to pattern large-areas with a resolution below 10 nm that could actually serve for both HUD holes and HUD network.…”
Section: Light Trapping Mechanism and Design Optimisationmentioning
confidence: 99%
“…They are obtained by the polymer-blend-lithography method and developed as light-trapping substrates for photovoltaic applications (for more details, see Ref. [34]). The diameters of the obtuseangled nanopillars range from 200 nm to 450 nm and their average height is 80 nm (a non-negligible height dispersion, ranging from 70 nm to 100 nm, remains).…”
Section: Resultsmentioning
confidence: 99%